Identification of nucleopolyhedrovirus that infect Nymphalid butterflies Agraulis vanillae and Dione juno - Rodríguez, Vanina Andrea (2011)
Dione juno and Agraulis vanillae are very common butterflies in natural gardens in South America, and also bred worldwide. In addition, larvae of these butterflies are considered as pests in crops of Passiflora spp. For these reasons, it is important to identify and describe pathogens of these species, both for preservation purposes and for use in pest control. Baculoviridae is a family of insect viruses that predominantly infect species of Lepidoptera and are used as bioinsecticides. Larvae of D. juno and A. vanillae exhibiting symptoms of baculovirus infection were examined for the presence of baculoviruses by PCR and transmission electron microscopy. Degenerate primers were designed and used to amplify partial sequences from the baculovirus p74, cathepsin, and chitinase genes, along with previously designed primers for amplification of lef-8, lef-9, and polh. Sequence data from these six loci, along with ultrastructural observations on occlusion bodies isolated from the larvae, confirmed that the larvae were infected with nucleopolyhedroviruses from genus Alphabaculovirus. The NPVs from the two different larval hosts appear to be variants of the same, previously undescribed baculovirus species. Phylogenetic analysis of the sequence data placed these NPVs in Alphabaculovirus group I/clade 1b.